Factors Influencing Informal Workers’ Decision to Participate in Employment Social Security With a Logistic Regression Approach - Annisa Yasfa Azhara; Mikhratunnisa Mikhratunnisa (Jurnal Varian, 2026)
Informal sector workers account for 59.40% of Indonesia’s total workforce, yet their access to social security protections remains inadequate. Enrollment in the Employment Social Security (BPJS Ketenagakerjaan) program, which serves as a formal social protection mechanism, is also notably low among this group. This situation points to various determinants shaping informal workers’ decisions about program participation. The purpose of this study is to examine factors affecting the enrollment decisions of informal sector workers in Sumbawa Sub-district regarding the Employment Social Security program. A quantitative approach was employed, utilizing Binary Logistic Regression to analyze primary data collected via questionnaires. The explanatory variables consist of age, education, number of dependents, income, monthly expenditure, gender, and marital status. The results show that the independent variables collectively have a substantial impact on participation decisions. Individually, age, education, number of dependents, income, and monthly expenditure show significant effects, whereas gender and marital status do not. Odds ratio analysis indicates that older age is associated with a reduced likelihood of participation (OR = 0.971). Individuals holding a bachelor’s degree have 3.859 times higher odds of enrolling than those with elementary education, the reference category. Additionally, each extra dependent lowers participation odds (OR = 0.807), higher income slightly increases participation (OR = 1.0000006), while higher monthly spending reduces it (OR = 0.9999995). Overall, participation decisions are more strongly shaped by economic and human capital considerations than by demographic attributes. These findings could inform policy strategies designed to expand participation coverage among informal sector workers.